Agrarian policy of the land liberal movement in the north of Left Bank Ukraine in the 1980s. XIXth - Kotelnytskyi, Nazar (Ukrainian Peasant, 2024)
Abstract. Purpose. The article examines the agrarian policy of the Zemstvo liberal movement in the north of Left Bank Ukraine in the 80s of the 19th century. The purpose of the proposed work is to find out, based on the analysis of historical primary sources, some of which are being introduced to international scientific circulation for the first time, the main components of the indicated direction in the ascetic activity of the opposition aristocratic front of the region at the stage of the 80s of the XIX century. Conclusion. The author came to the conclusion that in the 80s of the XIX century. the attitude of the opposition aristocratic front of northern Ukraine to the agrarian issue has changed significantly compared to previous periods. Already in 1881 liberal citizens of the region boldly declared not only the need for a substantive consideration of the concept of municipalization of the land fund of the Chernihiv province as a leading tool for providing the peasant society with private land allotments, but also proposed a specific financial and economic model for the practical implementation of this idea. Let us emphasize the fact of the partial victory of the Zemstvo liberals over the Russian autocracy in the field of tax and fiscal policy. Thanks to the ascetic efforts of the oppositionists, who persistently sent petitions to the supreme authority for the cancellation or significant reduction of ransom payments of the temporarily obligated peasantry, the indicated fiscal fees were radically reduced by the personal will of Emperor Alexander III. Congresses of farmers of the Chernihiv province, which were held with the support and patronage of the Zemstvo opposition of the region, were of great importance for the development of the agricultural sector of the economy of the Northern Left Bank. The mentioned forums became not only bodies of coordination and management of agricultural production development processes, but also a scientific-methodological and consultative-advisory institute for the advancement of agricultural science in the region. A significant achievement of the Zemstvo liberals was the founding and creation of the Chernihiv Agricultural Society. The organization became a popular public association, which was also engaged in demonstrating leading international experience in the field of agricultural production at the level of technologies and tools. In general, we can state that in the 80s of the XIX century. the agrarian policy of the Zemstvo liberal movement in the north of Left Bank Ukraine was significantly transformed and was based on the search for various options for the progressive evolution of the field of agricultural production and the society of peasant communities.